2010
DOI: 10.1021/ol101606v
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 2-Aza-Cope-[3 + 2] Dipolar Cycloaddition Strategy for the Synthesis of Quaternary Proline Scaffolds

Abstract: A one-pot multicomponent procedure for the synthesis of highly functionalized pyrrolidine rings through a domino 2-aza-Cope-[3+2] dipolar cycloaddition sequence has been demonstrated. This protocol was found to be both high yielding and stereoselective for the endo-cycloadduct.The pyrrolidine ring represents a prevalent scaffold for many compounds of pharmaceutical interest as well as a structural element common to the Amaryllidaceae and Erythrina alkaloids. 1 The development of mild, efficient, and operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Waters and co-workers combined a similar condensation/aza-Cope reaction with silver-mediated [3+2] cyclo-addition in a consecutive reaction trio. [102] …”
Section: [33]-sigmatropic Rearrangementsmentioning
confidence: 99%
“…Waters and co-workers combined a similar condensation/aza-Cope reaction with silver-mediated [3+2] cyclo-addition in a consecutive reaction trio. [102] …”
Section: [33]-sigmatropic Rearrangementsmentioning
confidence: 99%
“…workers synthesized allylglycine derivatives from α-substituted homoallylamines through a cationic aza-Cope rearrangement and iminium ion solvolysis. [14] Waters et al prepared scaffolds of indolizidines through an aza-Cope-[3+2] dipolar cycloaddition followed by an aza-Prins cyclization using trifluoroacetic acid (TFA) and water as attacking nucleophiles to trap the intermediate carbocation [15] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although our original experimental conditions for ylide formation employed a molar excess of AgOAc, 8 we have now observed that the process can be conducted catalytically (10 mol%) with no deleterious effect on the overall yield. Indeed, the use of Et 3 N (2.0 equiv) and AgOAc (0.1 equiv) furnished an N –metalated azomethine ylide intermediate that underwent endo -selective [3+2] dipolar cycloaddition in the presence of dipolarophiles 5a–b , providing the highly functionalized 2-allylpyrrolidines 6a–f (Table 1) as single diastereomers in good overall yields.…”
Section: Resultsmentioning
confidence: 98%
“…8 Condensation of a homoallylic amine (cf. 4 , Scheme 1) with ethyl glyoxylate affords an imine ( I ), which is positioned to undergo 2-aza-Cope rearrangement 9 to furnish an azomethine ylide precursor ( II ).…”
Section: Introductionmentioning
confidence: 99%